Pengaruh Persepsi Karakteristik Pekerjaan dan Dukungan Organisasi Terhadap OCB dengan Mediasi Komitmen Pertumbuhan dan Normatif Karyawan - Theresia Yunie Puspita (Jurnal Ilmiah Infokam, 2020)
This research aims to determine the effect of perceptions of job characteristics and organizational support for OCB by mediating growth commitment and normative commitment of employees in the Engineering Division at PT. Adya Graha Surabaya. This research uses a quantitative approach that focuses more on hypothesis testing, while the data analysis technique uses path analysis, which looks at the relationship between job characteristics and organizational support felt by employees towards OCB through mediating growth commitments and employee normative commitments. The research findings indicate that perceived job characteristics significantly influence employee growth commitments, and employee growth commitments have a significant relationship with OCB, and also indicate that perceived job characteristics significantly influence OCB by mediating employee growth commitments. The results also show that perceived organizational support significantly influences employees' normative commitment, and normative commitment significantly influences OCB.